Analysis Of The Effect Of Financial Distress On Trust Financial Report - Setiawan, Indra; Dharma, Dias Adi (Indonesian Journal Economic Review (IJER), 2025)
This paper investigates the impact of financial distress on financial statement trustworthiness. State-owned holding companies from Indonesia were selected for diagnostic analysis on the basis that Structural Equation Modeling (SEM) could be implemented by Partial Least Squares(PLS). The result shows that financial distress is worsba than the confidence in financial reports based on. Companies under financial stress have more broken and less timely financial statements, causing confidence in their Financial information to diminish likewise. The findings underscore the importance of keeping the economy stable to protect the integrity of financial information. Because there are distinct regulatory and financial characteristics for state-owned businesses this analysis highlights how financial distress can imperil information disclosure. Research can take a case-study, official interview and incorporate methods of more qualitative nature in order to further explore the links between financial distress and stakeholder trust. In its significance to policy makers, service providers and managers in state-owned enterprises these conclusions remind us that greater financial discipline and risk management are needed for such against a backdrop of stiffer financial examination.